2023
DOI: 10.1021/jacs.3c00321
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Mediated Separation and Reversible Transformation of 1D Supramolecular Polymorphs Built from [W10O32]4– Templated 48-Nuclei Silver(I) Cluster

Abstract: Although the C−H•••O interaction is an essential component in determining the molecular packing in solids and the properties in supramolecular chemistry, it presents a significant challenge when trying to use it in the crystal engineering of complex metallosupramolecules, even though it is a relatively weak supramolecular force. The first pair of highnuclearity silver-cluster-based one-dimensional (1D) polymorphs built from supramolecular synthon [W 10 O 32 @Ag 48 (CyS) 24 (NO 3 ) 16 ]•4NO 3 (Cy = cyclohexyl) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Generally, energy transitions in photophysical processes are primarily depicted by the Jablonski diagram, which includes the following procedures: excitation (or absorption), vibrational relaxation (heat release), radiative emission (fluorescence), and non-radiative transition (heat release). 63–65 No fluorescence was observed for Ti2 , Ti8 , and Ti16 . Therefore, absorption must be considered as the primary factor influencing photothermal conversion performance.…”
Section: Resultsmentioning
confidence: 98%
“…Generally, energy transitions in photophysical processes are primarily depicted by the Jablonski diagram, which includes the following procedures: excitation (or absorption), vibrational relaxation (heat release), radiative emission (fluorescence), and non-radiative transition (heat release). 63–65 No fluorescence was observed for Ti2 , Ti8 , and Ti16 . Therefore, absorption must be considered as the primary factor influencing photothermal conversion performance.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, Sheng et al reported the first supramolecular polymorphs of high-nuclearity Ag 48 NCs encapsulated in an anionic template via solvent mediation. 266…”
Section: Chemical Reactivity Of Ligand-protected Atomically Precise M...mentioning
confidence: 99%
“…Solvents, act as crucial reaction participant in the wet synthesis of metal nanoclusters, with their roles being empirically summarized into two key aspects: (1) the solvation interaction between solvents and precursors governs the formation of nanocluster species; and (2) subsequent desolvation processes guide crystallization behaviors, playing a pivotal role in both the formation and crystallization of metal nanoclusters. Therefore, the design and fabrication of solvent-mediated superatomic Cu NCs are significantly important for gaining in-depth understanding of the solvation effect that dominates their assembly process and subsequent crystallization outcomes.…”
Section: Introductionmentioning
confidence: 99%